Desa Wisata Tegaren: Sadewa, Jadesta, Adwi dan Persepsi Sosial Publik Terhadap Kemajuan Desa Wisata - Praja Firdaus Nuryananda; Joko Mijiarto; A. Muammar Alawi; Wahyuni Wahyuni (STIEPAR YAPARI Bandung, 2023)
It has been four years since the process of developing a tourism village in Tegaren has been going on since 2019. Appreciation to the hard work of all parties involved in raising a tourism village in Tegaren, this village, which is located in the northern part of Trenggalek, has made several achievements. In addition to being one of the Seratus Desa Wisata villages that were fostered directly by Trenggalek Regency, Tegaren has succeeded in becoming the top 500 Anugerah Desa Wisata Indonesia 2022 and won third place at the local Soetran Award. The research team later found that with this series of achievements, the progress of developing tourism villages in Tegaren ultimately created positive social perceptions from stakeholders in Tegaren and the wider village community. By using interview instruments, questionnaires, and literature studies, the research team assessed that this perception was formed due to three things, including 1) the increasing attention that Tegaren received from the Trenggalek Regency government and the agencies under it, 2) the more trusted Tegaren to be the organizer of the official activities by the Trenggalek Regency government, and 3) the existence of village original income (pendapatan asli desa/PAD) from the tourism sector which this time became the first time Tegaren received PAD from the tourism sector. The three results of confirmation of the positive perception are verification of the success of the community-based tourism concept in developing rural tourism.